Destruction and its impact on ancient societies at the end of the Bronze Age - Millek, Jesse, (Lockwood Press, 2023)
"This volume offers a groundbreaking reassessment of the destructions that allegedly occurred at sites across the eastern Mediterranean at the end of the Late Bronze Age, and challenges the numerous grand theories that have been put forward to account for them. The author demonstrates that earthquakes, warfare, and destruction all played a much smaller role in this period than the literature of the past several decades has claimed, and makes the case that the end of the Late Bronze Age was a far less dramatic and more protracted process than is generally believed"--